A nomogram based on tumor response to induction chemotherapy may predict survival in locoregionally advanced nasopharyngeal carcinoma. Issue 6 (25th February 2022) - Jiang, Yu‐Ting; Chen, Kai‐Hua; Liang, Zhong‐Guo; Yang, Jie; Wei, Si‐Qi; Qu, Song; Li, Ling; Zhu, Xiao‐Dong
Abstract: Background: To evaluate the clinical significance of tumor response to induction chemotherapy (IC) in locoregionally advanced nasopharyngeal carcinoma (LANPC) patients and further to develop a nomogram for predicting survival prognosis. Methods: A total of 498 patients with stage III‐IVA NPC applying IC and concurrent chemotherapy were reviewed (training cohort, n = 376; validation cohort, n = 122). Results: Tumor response was an independent predictor for clinical outcomes. The nomogram included age, N stage, pretreatment Epstein–Barr virus DNA, lymphocyte‐to‐monocyte ratio, and tumor response achieved an ideal C‐index of 0.703 (95% CI 0.655–0.751) in the validation cohort for predicting overall survival (OS), which outperformed than that of the TNM system alone (C‐index, 0.670, 95% CI: 0.622–0.718). In addition, the nomogram could successfully classified patients into different risk groups. Conclusions: We established and validated a precise and convenient nomogram based on tumor response for predicting the OS of LANPC patients.